Centralizing the knowledge and interpretation of pain in Chemotherapy-Induced Peripheral Neuropathy: a paradigm shift towards brain-centric approaches - Mário Manuel Correia de Vasconcelos Campos Cunha (2024)
Chemotherapy-induced peripheral neuropathy (CIPN) is one of the side effects of cancer treatment, often linked with pain complaints. Patients report mechanical and thermal hypersensitivity that may emerge during chemotherapy treatment and persist after the end of chemotherapy. Whereas the latter situation disturbs the quality of life, life itself may be endangered by the emergence of CIPN during cancer treatment. The causes of CIPN have almost entirely been ascribed to the neurotoxic effects of chemotherapeutic drugs at the peripheral nervous system, but the central consequences of peripheral neuropathy are starting to be unraveled, namely at the supraspinal pain modulatory system. Based on our interests in the field, we undertook a narrative critical of the brain-centered signatures that may underpin chemotherapy-induced neuropathic pain, along with a translational analysis of the clinical presentation, evaluation, and treatment of CIPN. The changes in the of descending pain modulation in CIPN models along with the functional and connectivity abnormalities in the brain of CIPN patients is analyzed A translational analysis of preclinical findings about descending pain regulation during CIPN is reviewed taking into account the neurochemical systems (serotonin and noradrenaline) that are targeted in CIPN management in patients, namely antidepressants. In conclusion, this study highlights the importance of studying supraspinal areas, namely those that target the spinal cord, to understand the pathophysiology of CIPN, allowing more personalized and effective CIPN treatments.